Rereading Ambiguity in Ahmadrezā Ahmadī’s Pattern based on William Empson's Theory - Nematollah Iranzadeh; Mozhghan Jafarmanesh (مطالعات زبانی و بلاغی)
As one of the components of Iranian poetry and art, ambiguity was put forward with the tendency of modern aesthetic taste to read ambiguous texts and to highlight the role of the audience in receiving meaning, especially after the rise of romanticism. By using polysemy and creating conceptual gaps in the structure of the poem, the modern poet creates lasting, creative, and dynamic literature. In this article, Ahmad Rezā Ahmadī’s (1940) poetry collection, Pattern has been investigated concerning its aspects of ambiguity, based on William Empson's (1906-1984) point of view in Seven Types of Ambiguity. This qualitative and quantitative research has a conceptual model and involves questions. The content analysis technique is used to collect data which is then analyzed, employing William Empson's theory of ambiguity. By examining new-wave poetry based on the types and the degree of ambiguity, we will recognize new horizons of aesthetics that will help us improve our interpretation skills and enjoy modern poetry more. By introducing new-wave poetry in his collection Pattern (1962), Ahmadī tries to embed the social content of his poems in the structural and linguistic ambiguities. Language, structure, and content are intertwined in his poetry in such a way that the content itself is a part of the structure and language games. Scattered and contradictory imagery, assimilation and repetition, ambiguity and uncertainty indicate that Pattern is composed by an improvisational, hesitant, and of course creative mind, and it requires an enthusiastic and active reader to delve into the texts.